Seeing Sibudu seeds: an illustrated text of the more frequent Middle Stone Age stones, nuts and seeds - Wintjes, J.; Sievers, C. (Southern African Humanities, 2021)
The seven most common stones, nuts and seeds identified in the Middle Stone Age layers at Sibudu Cave are illustrated and described. Descriptions focus on diagnostic features of the archaeological specimens. The illustrations and accompanying text are intended to characterise the Sibudu assemblage and also to contribute towards the establishment of identification literature that can be used by other archaeobotanists. To cite this article: Wintjes, J. & Sievers, C. 2006. Seeing Sibudu seeds: an illustrated text of the more frequent Middle Stone Age stones, nuts and seeds. Southern African Humanities 18(1): 223-33.